ANALISIS KAPABILITAS PROSES UNTUK PENGENDALIAN KUALITAS AIR LIMBAH DI INDUSTRI FARMASI - Dino Rimantho; Athiyah Athiyah (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2019)
The management of wastewater should produce the final result of its corresponding environmental quality standards. Thus, that it does not harm the environment and decreasing the quality of human health. The problem on this research was found that there are several parameters on the wastewater not comply such as pH and TSS to Indonesian Standards. This study aims to analyze the value of process capability resulting from wastewater treatment, especially parameters of pH and TSS. Several methods used in this study such as IMR control chart, capability process, and fishbone. The results of this study show the parameters of pH and TSS from the wastewater treatment in the pharmaceutical industry obtained the average Cp index of around 0.602 and CPK approximately 0.8 for pH parameters. In addition, the quality of wastewater for TSS parameters obtained CP index roughly 0.68 and CPK approximately 0.70. Therefore, it can be concluded that the process does not have a good capability.